Соціально-економічний стан домогосподарств України в умовах війни. - Завадських, Ганна Миколаївна; Zavadskykh, Hanna (Харків: ДБТУ, 2024)
UKR У статті проаналізовано соціально-економічний стан домогосподарств в умовах війни, в основі аналізу – результати загальнодержавного вибіркового обстеження соціально-економічного стану домогосподарств (ОСЕСД), доповнені даними Державної служби статистики за 2021–2023 роки. Узагальнено результати оцінки домогосподарствами купівельної спроможності своїх доходів. Досліджено динаміку зміни і структуру реальних доходів домогосподарств. Викладено оцінку впливу війни на соціально-економічний стан домогосподарств. |||||||||||||||| ENG The article presents the results of an analytical study of the socio-economic status of households in Ukraine in 2023 compared to 2021. The dynamics, trends and structure of real incomes of households were studied. An analysis of households' self-assessment of the purchasing power of income was carried out. Participation of households in state social assistance programs. Compared to 2021, the average monthly real income of households increased by UAH 669. As in 2021, households with children had higher levels of income than households without children – UAH 19,101. against UAH 13,711 This is due to the fact that the second group includes all households consisting exclusively of pensioners. The analysis of the structure of household incomes indicates the following main structural changes in 2023 compared to 2021: a significant increase in the share of using savings and loans – 5.6% in 2023 against 1.3% in 2021, and in households with many children this share reached 16.8%. Despite the hostilities, Ukrainians demonstrate impressive resilience. An important source of household income in Ukraine is social assistance and other received current transfers, which include pensions, scholarships, benefits, subsidies and compensation payments provided in cash State social assistance to low-income families and IDP assistance – the main types of assistance – these two types of assistance have the largest specific weight among all households receiving social support. The results of the survey indicate that although the majority of households are experiencing financial difficulties, their self-assessment of the quality of life turned out to be much higher than expected. The share of households that received state financial support under various programs during the research period is given. Estimates of the impact of the war on the socio-economic condition of domestic households are presented.
SOCIO-ECONOMIC STATE OF HOUSEHOLDS OF UKRAINE UNDER THE CONDITIONS OF MARITAL STATE
Keywords: домогосподарство; купівельна спроможність; структура доходів; заощадження; соціальна допомога; рівень бідності.; household; purchasing power; income structure; savings; social assistance; poverty level